P‐32: 4K‐UHD Broadcast Monitor Display System Based on FPGA. Issue 1 (28th June 2021) - Geng, Lihua; Wu, Congrui; Rao, Tianmin; Wang, Xian; Duan, Ran; Zhang, Xiao; Ma, Xitong
Abstract : The system introduced by the paper is a 4K‐UHD Broadcast Monitor Display System developed by BOE, it has been applied to a BOE 4K BD‐Cell LCD Broadcast Monitor production. The hardware and software architecture of the system is based on FPGA. The system is the first monitor system which supports up to eight 12G‐SDI interfaces (Eight Inputs and Eight Outputs). The System has a powerful image quality processing engine, including Up‐Scaler, RGB Processor, Gamma Curve Adapter, and especially a real 33*33*33 dimension of 3D‐LUT (Look‐Up Table) which can substantially enhance the display performance. In addition, the system also supports a variety of broadcast monitor functions such as Waveform, Focus Assist, Histogram, and so on.